THE ANALYSIS OF THREE APPROACHES IN SYNTAX (TRADITIONAL GRAMMAR, IMMEDIATE CONSTITUENT ANALYSIS AND TRANSFORMATIONAL GRAMMAR): THEIR STRENGTHS AND WEAKNESSES IN MARITIME ENGLISH CONTEXT - Sri Sartiini (Sekolah Tinggi Maritim Yogyakarta, 2015)
There are many approaches to analyze English sentence formations. Each approach has got different view upon the analysis of the sentence formation. The aim of this paper is to compare three approaches and this paper tries to compare the use of those three approaches in the production or analysis of English sentences applied in maritime english context. This study is a type of a library research. The conclusion of this paper shows that there are some differences in the perspective use of each approach. Traditional Grammar more focusses on the correct arrangement of the word in the native language and it is based on meaning. Besides it is also based on written language which is considered better than spoken language. Immediate Constituent Analysis focusses the analysis more on the relation of each constituent in a sentence rather than on how the sentence is constructed. Whereas Transformational Grammar which studies on internal language or it is called competence focusses on the grammar which is assumed as a model or systematic description of linguistics competence. From the study It is also known that each syntax approach has their own strengths and weaknesses regarding their use in maritime english subject.